HEALTHCARE ON WHEELS: SOCIAL AND ECONOMIC OUTCOMES OF THE MOBILE DISPENSARY INITIATIVE BY TATA POWER DDL - Kumar, Vikramendra (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper focuses on the social and economic impacts of Mobile Dispensary Initiative of Tata Power DDL in the JJ colony of North and West Delhi. Using an ethnographic research approach, based on their perceptions of the mobile health care services. The results show positive changes in health literacy concerning the availability of primary healthcare services to disenfranchised populations. Participants expressed the fact that they were experiencing low healthcare bills as well as the efficient delivery of services therefore the key role of the initiative to the improvement of economic stability was evident. Also, quantitative data collected through interviews, surveys, and direct observations gave a more social aspect of the social relations and community mobilization supported by the mobile dispensaries. This study emphasizes the need to come up with new solutions to some of the health issues affecting the urban dwellers and supports the incorporation of corporate social responsibility programs into the public health framework. Finally, the research provides policy implications for the extension of mobile health service and the exploration of the effects on the well-being of a community.